Technology-Enhanced Self-Study Learning Tool: An Approach to Improve Students Skills - Patil, Sharad D.; Pawar, Rajendra V.; Patil, Ajinkya K.; Jalwadi, Sudhindra N. (Journal of Engineering Education Transformations, 2025)
In the engineering education system, the student’s learning styles and abilities to acquire new skill sets have been transformed drastically due to the rising use of technology. The study provides a novel approach to self-learning through the use of technology-enhanced techniques aimed to improve student skills. The tool leverages digital platforms and interactive resources to create an engaging and personalized learning environment. This paper presents an examination of the effectiveness of a technology-enhanced self-study learning tool in enhancing student abilities such as knowledge, use of IT tools, communication, and information sharing across several disciplines. The tool’s architecture integrates adaptive learning, multimedia content, and assessment mechanisms that adapt to individual learning styles and pace. This study intends to evaluate the tool’s influence on improving students’ knowledge, retention, and application of subject matter by examining user interactions and performance data. The methodology used is focused on a particular topic, data collection through the use of all multimedia resources, presentation, posting of videos, peer review, and comments on each task to improve abilities. With the deployment of technology-enhanced techniques, students’ skills were observed to improve; around 8% of students’ skills were improved in the internal evaluation.